Predicting Bullying Behavior from Victimization Experiences to Strengthen Prevention Management in Islamic Early Childhood Education - Fifi Khoirul Fitriyah; Wiwik Afridah; Aris Sudaryanto; Nordin bin Mamat; Luthfiyah Nurlaela (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to evaluate the predictive relationship between the experience of being a victim of bullying and the tendency to become a perpetrator of bullying in early childhood, as well as to formulate its contribution to strengthening bullying prevention management in Islamic preschools. This study used a quantitative approach with a correlational-predictive design. The study sample included 398 early childhood students in Islamic preschools. Data were collected using the Revised Olweus Bullying/Victimization Questionnaire (OBVQ-R) adapted into Indonesian and completed by teachers based on structured observations. The instrument measures verbal, physical, and relational bullying as victim experiences and perpetrator actions. Data were analyzed using descriptive statistics and multiple multivariate regression. The results showed that the experience of being a victim of bullying predicted children's bullying behavior with an explanatory contribution of approximately 50.2% to 56.4%. Verbal bullying was the most consistent form because it predicted verbal, physical, and relational actions. Experiences of physical bullying most strongly predicted physical actions, while experiences of relational bullying predicted relational actions. This study concludes that children can learn and reproduce bullying behavior from their social experiences. These findings reinforce the importance of behavioral assessment, incident recording, counseling, family involvement, moral development, and safe classroom policies in managing bullying prevention in Islamic early childhood education. Further research is recommended to develop a bullying mitigation model based on an intelligent management system that integrates local Indonesian and Islamic values.